The dual-effects of PLGA@MT electrospun nanofiber coatings on promoting osteogenesis at the titanium–bone interface under diabetic conditions. Issue 21 (4th May 2022) - Wang, Zijie; Chen, Tingting; Wu, Zimei; Jiang, Xingzhu; Hou, Qiaodan; Miao, Sikai; Xia, Ruihao; Wang, Lin
Abstract : A novel therapeutic strategy for promoting titanium–bone interface bone integration under diabetic conditions by fabricating PLGA@MT electrospun nanofiber coatings. Abstract : The high failure risk of endosseous titanium implants under diabetes conditions appeals to strengthen the osteointegration on the titanium–bone (Ti–B) interface. Melatonin (MT) is a neurohormone involved in bone homeostasis, which can promote osteogenesis and inhibit ROS overproduction through multiple pathways, but its effects on the Ti–B interface in diabetes remain elusive. The biodegradable poly(lactic- co -glycolic acid) (PLGA) has excellent controlled and sustained release properties, low cytotoxicity, and biocompatibility. Our study fabricated a nanofiber in which MT was encapsulated in PLGA to generate a nanofiber coating on a polydopamine (PDA)-modified titanium surface using electrospinning technology. The surface characteristic showed that MT was fully encapsulated in the PLGA carrier, and PLGA@MT was strongly coupled to the titanium matrix. Furthermore, the PLGA@MT-Ti nanofiber could release MT for at least 30 days. In vitro cellular tests demonstrated that PLGA@MT-Ti directly stimulates osteogenesis on the Ti–B interface by activating the BMP-4/WNT pathway in a dose-dependent manner. The effect of suppressing diabetes-induced ROS overproduction and promoting cell proliferation was not proportional to the content of MT. In vivo experiments revealed that PLGA@MT-Ti screws promoted the bone formation and osteointegration in type 1 diabetes mellitus (T1DM) mice with tibial bone defects. Our findings demonstrate that PLGA@MT-Ti exerted dual effects through activating the BMP-4/WNT pathway and attenuating ROS overproduction to promote osteogenesis and osteointegration at the Ti–B interface, providing a novel strategy to fabricate biomaterial modification and biofunctionalization under diabetic conditions.